2018
DOI: 10.1186/s13072-018-0197-x
|View full text |Cite
|
Sign up to set email alerts
|

CREBBP/EP300 bromodomains are critical to sustain the GATA1/MYC regulatory axis in proliferation

Abstract: BackgroundThe reported antitumor activity of the BET family bromodomain inhibitors has prompted the development of inhibitors against other bromodomains. However, the human genome encodes more than 60 different bromodomains and most of them remain unexplored.ResultsWe report that the bromodomains of the histone acetyltransferases CREBBP/EP300 are critical to sustain the proliferation of human leukemia and lymphoma cell lines. EP300 is very abundant at super-enhancers in K562 and is coincident with sites of GAT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 50 publications
3
45
0
Order By: Relevance
“…Importantly, JQ1 also causes an increase in the percentage of cells in G0/1 that correlates with the overlap in transcriptional changes caused by JQ1 and the TAF1 knock down. Importantly, we have previously described that CBP30 also increases the number of cells in G0/1 in K562 [8] which also correlates with the overlap in transcriptional responses to CBP30 and TAF1 knock down. In Importantly, the analysis of enrichment in genomic features revealed that even though BAY-299 and the TAF1 knock down downregulated the expression of genes occupied by TAF1, BAY-299 specifically downregulated the expression of genes that in addition have very high levels of acetylation at their promoters.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…Importantly, JQ1 also causes an increase in the percentage of cells in G0/1 that correlates with the overlap in transcriptional changes caused by JQ1 and the TAF1 knock down. Importantly, we have previously described that CBP30 also increases the number of cells in G0/1 in K562 [8] which also correlates with the overlap in transcriptional responses to CBP30 and TAF1 knock down. In Importantly, the analysis of enrichment in genomic features revealed that even though BAY-299 and the TAF1 knock down downregulated the expression of genes occupied by TAF1, BAY-299 specifically downregulated the expression of genes that in addition have very high levels of acetylation at their promoters.…”
Section: Discussionsupporting
confidence: 56%
“…We next investigated which transcriptional pathways could be affected by the TAF1 knock down and BAY-299 treatment. Our previous work showed that CBP30 downregulates both the GATA1 and MYC-dependent transcriptional signature in K562 [8]. Like CBP30, sh670 and BAY-299 downregulated genes typically upregulated by MYC and targets of GATA1 in K562 ( Figure 3A).…”
Section: Supplementarymentioning
confidence: 84%
See 1 more Smart Citation
“…Our previous work has demonstrated that CREBBP/EP300 bromodomain inhibitors are able to displace CREBBP and EP300 from acetylated genomic regions resulting in lower levels of histone acetylation at these sites (16). Therefore, we asked whether CREBBP/EP300 bromodomain inhibitors could be reducing the levels of H3K27ac at AR-binding sites located in SEs (see Supplementary Fig.…”
Section: Crebbp/ep300 Bromodomain Inhibitors Downregulate the Levels mentioning
confidence: 99%
“…Prompted by the preclinical success of BET bromodomains inhibitors, dual inhibitors of the bromodomains of CREBBP and EP300 have been recently developed (9)(10)(11)(12)(13)(14)(15). These inhibitors mediate several biological responses including antiproliferative effects in hematologic cancer cell lines, such as leukemia (11,13,16) and multiple myeloma (17) cell lines, and AR-positive prostate cancer cell lines (15). Moreover, EP300/CREBBP bromodomain inhibitors interfere with important oncogenic transcription programs driven by transcription factors such as MYC, IRF4, GATA1, and AR (13,(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%